2003
DOI: 10.1002/jbm.b.20016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tranexamic acid in fibrin sealant on adhesion formation in the rat

Abstract: The objective of the research was to determine the effect of the type, dose, and volume of anti-fibrinolytic agents (tranexamic acid, aprotinin) added to fibrin formulations, on adhesion development. Adhesions were induced in 228 male rats by creating apposing parietal and visceral peritoneal defects. Animals were randomized to receive no treatment or a fibrin formulation containing aprotinin or tranexamic acid. Seven days later the incidence of adhesions, and the force and energy required to detach them, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The seal formed with sealant 3 appears to be more secure postoperatively, resulting in a lower incidence and severity of re-bleeding. This may be at least partly attributable to tranexamic acid (nominal 95 mg/ml) in the formulation of sealant 3, Quixil [9,10] .…”
Section: Discussionmentioning
confidence: 99%
“…The seal formed with sealant 3 appears to be more secure postoperatively, resulting in a lower incidence and severity of re-bleeding. This may be at least partly attributable to tranexamic acid (nominal 95 mg/ml) in the formulation of sealant 3, Quixil [9,10] .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have been conducted with Adhexil in both abdominal wounds (rat models) and uterine horn wound (rabbit models). These studies have shown effectiveness of this product in prevention and/or reduction of postsurgical adhesions, in both the absence and presence of bleeding (27,28).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the severest adhesion formation could receive a score of 12. Second, the maximum force required to detach the adhered cecum completely was determined using a piezo-electrical device, as described in a previous report (Wiseman et al, 2004). Finally, the cecum and intestine were opened along the mesenteric attachment for performance of planimetry (Muller et al, 2003).…”
Section: Methodsmentioning
confidence: 99%